Železnodobno naselje Most na Soči = The Iron Age Settlement at Most na Soči Razprave = Treatises - Dular, Janez; Tecco Hvala, Sneža (Opera Instituti Archaeologici Sloveniae, 2018)
The second volume on the Iron Age settlement at Most na Soči evaluates from various aspects the structures and small finds that has been presented in the first book.